2020
DOI: 10.1016/j.joca.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Lumican is upregulated in osteoarthritis and contributes to TLR4-induced pro-inflammatory activation of cartilage degradation and macrophage polarization

Abstract: Objective: Lumican (LUM) is a major extracellular matrix glycoprotein in adult articular cartilage and its expression is known to be upregulated upon cartilage degeneration. LUM is associated with the pathogen-associated molecular pattern (PAMP) activation of the TLR4 signalling cascade, with TLR4 being highly associated with inflammation in rheumatic diseases. However, the main role of the LUM structural molecule in osteoarthritis (OA) remains elusive. The aim of this study was, therefore, to understand the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
2
32
0
1
Order By: Relevance
“…At the pathophysiological level , LUM promotes LPS-induced TLR4 activation, which finally leads to extensive cartilage degradation. Besides, the co-stimulation of LUM and LPS also promotes macrophage activation and causes polarization towards the M1 phenotype [ 63 ].…”
Section: Macrophages Are An Emerging Target For Oa Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…At the pathophysiological level , LUM promotes LPS-induced TLR4 activation, which finally leads to extensive cartilage degradation. Besides, the co-stimulation of LUM and LPS also promotes macrophage activation and causes polarization towards the M1 phenotype [ 63 ].…”
Section: Macrophages Are An Emerging Target For Oa Treatmentmentioning
confidence: 99%
“…Very recently, Barreto and colleagues demonstrated that intact LUM in synovial fluid enhances the LPS-induced inflammatory response in a TLR4-dependent manner, indicating that LUM may promote the formation of OA through this pathway [ 23 , 64 ]. In terms of signaling pathways , LUM significantly activates the NF-kB signaling pathway in macrophages in OA joints [ 63 ]. In summary, LUM exacerbates the process of inflammation by acting on macrophages in OA joints.…”
Section: Macrophages Are An Emerging Target For Oa Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Mahon and co-workers showed that basic calcium phosphate crystals cause an M1-like macrophage differentiation, accompanied with a shift towards glycolytic energy metabolism, which has been shown to control inflammatory macrophage functions [12,13]. Another study demonstrated that the cartilage extracellular matrix protein lumican was increased in the synovial fluid (SF) from OA patients and augmented LPS-induced TLR4 signaling, which associated with increased expression of M1-like and decreased expression of M2-like macrophage markers [14].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…[ 62 ] Also, work by Haltmayer et al showed in a model using horse osteochondral explants, where OA was induced by partial thickness defect in presence of proinflammatory cytokines (TNF‐α and IL‐1β), that MMP and IL‐6 expression were increased upon OA induction, and coculture with synovial membranes increased nitric oxide levels indicating M1 synovial macrophage polarization and improving the similarity of the model to physiological OA. [ 63 ] Two recent studies used a human OA cartilage explant model to demonstrate that exposure to Lumican, a small leucine‐rich proteoglycan that the author found upregulated in OA patient serum, when combined with LPS could activate cartilage degradation, with loss of proteoglycans, downregulation of COL2, and surface fibrillation; [ 64 ] and that physiological compression could modulate the inflammatory microenvironment and ECM composition. [ 65 ]…”
Section: From Basic To Advanced Cartilage Models: New Strategies To Dmentioning
confidence: 99%